2007
DOI: 10.1124/jpet.107.124719
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Airway Responses to Influenza A/PR/8/34 by Δ9-Tetrahydrocannabinol in C57BL/6 Mice

Abstract: ⌬ 9-Tetrahydrocannabinol (⌬ 9 -THC) has been widely established as a modulator of host immune responses. Accordingly, the objective of the present study was to examine the effects of ⌬ 9 -THC on the immune response within the lungs and associated changes in the morphology of the bronchiolar epithelium after one challenge with a nonlethal dose of the influenza virus A/PR/8 (PR8). C57BL/6 mice were treated by oral gavage with ⌬ 9 -THC and/or vehicle (corn oil) for 5 consecutive days. On day 3, mice were instille… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
53
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 32 publications
(34 reference statements)
3
53
1
Order By: Relevance
“…Little is known about the role of IL-17 in viral pulmonary infections; it has been suggested that an IL-17 receptor agonist antagonizes the response to influenza virus challenge (12), but our results and those of others (22,50) indicate that Th17 cells can be involved in protection against influenza virus. Whereas other studies using immunosuppressive agents report exacerbated influenza disease (7,46), in this study, CT-treated mice appeared to develop initial Th1/Th17 inflammatory responses that directly contributed to enhanced survival. In our experiments, the viral challenge was given 24 h after immunomodulator administration.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Little is known about the role of IL-17 in viral pulmonary infections; it has been suggested that an IL-17 receptor agonist antagonizes the response to influenza virus challenge (12), but our results and those of others (22,50) indicate that Th17 cells can be involved in protection against influenza virus. Whereas other studies using immunosuppressive agents report exacerbated influenza disease (7,46), in this study, CT-treated mice appeared to develop initial Th1/Th17 inflammatory responses that directly contributed to enhanced survival. In our experiments, the viral challenge was given 24 h after immunomodulator administration.…”
Section: Discussionmentioning
confidence: 56%
“…However, immunomodulation does not always result in beneficial responses to infection. Administration of ⌬ 9 -THC, an immunosuppressive compound, decreased cellular infiltration and increased viral load when given prior to and during influenza virus infection (7). Similarly, sphingosine 1-phosphate (S1P) analog, an immunotherapeutic agent, was found to suppress induction of T-cell responses to influenza virus (46).…”
mentioning
confidence: 99%
“…The lungs were removed, formalin fixed, and paraffin embedded for hematoxylin and eosin (H&E) staining according to standard methods. Inflammatory changes on the basis of numbers of inflammatory cells and tissue damage in the lungs were determined by histology from H&E-stained longitudinal cross-sections and graded as no change (score ϭ 0), mild (score ϭ 1), moderate (score ϭ 2), or severe (score ϭ 3) as previously described (2). Sections were reviewed and scored in a blind fashion by a pathologist (C.-C.L.).…”
Section: Methodsmentioning
confidence: 99%
“…The images were analyzed by use of an inverted microscope (Olympus, Japan). Lung pathology was assessed by the histopathological scoring system as previously described (3,54).…”
Section: Methodsmentioning
confidence: 99%